2018
DOI: 10.1159/000489888
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of End-Tidal Capnography Monitoring during Flexible Bronchoscopy in Nonintubated Patients under Sedation: A Randomized Controlled Study

Abstract: Background: Although appropriate sedation is recommended during flexible bronchoscopy (FB), patients are at risk for hypoventilation due to inadvertent oversedation. End-tidal capnography is expected as an additional useful monitor for these patients during FB. Objectives: The aim of this study was to evaluate the benefit of additional end-tidal capnography monitoring in reducing the incidence of hypoxemia during FB in patients under sedation. Methods: Patients undergoing FB under moderate sedation without tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
11
1
3
Order By: Relevance
“…It has been published that the nadir on SpO 2 decline could be delayed by 45-60 seconds after an apnea episode (18). The capnographic monitoring allows for the earlier detection of apnea episodes in patients undergoing bronchoscopic examinations under midazolam sedation, more real measurement values of carbon dioxide than pulse oximetry (15,16). In our study, cap-ONE YG-227T (NIHON KOHDEN) detected the occurrence of apnea in patients undergoing a bronchoscopic examination under fentanyl and midazolam sedation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It has been published that the nadir on SpO 2 decline could be delayed by 45-60 seconds after an apnea episode (18). The capnographic monitoring allows for the earlier detection of apnea episodes in patients undergoing bronchoscopic examinations under midazolam sedation, more real measurement values of carbon dioxide than pulse oximetry (15,16). In our study, cap-ONE YG-227T (NIHON KOHDEN) detected the occurrence of apnea in patients undergoing a bronchoscopic examination under fentanyl and midazolam sedation.…”
Section: Discussionmentioning
confidence: 53%
“…Moderate sedation is necessary for safe bronchoscopy examination to prevent apnea and oxygen desaturation. End-tidal capnography monitored the occurrence of apnea episodes at a high frequency in patients during a bronchoscopic examination under midazolam sedation in a clinical setting (15,16). Here, we retrospectively revealed the occurrence of apnea episodes during bronchoscopic examinations under fentanyl and midazolam sedation by end-tidal capnography.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed the superiority of tPCO2 to end tidal CO2 and suggested that upper airway muscle weakness due to propofol is the reason that end tidal CO2 monitoring is not useful [9]. Another study reported that false apnea alarms occurred 83 times in 185 patients monitored by end-tidal CO2 capnography [7]. The current study aimed to reach the optimum sedation level necessary for the bronchoscopist to complete the procedure successfully.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported a correlation between end tidal CO2 and tPCO2 in volunteers and in spontaneously breathing patients in the intensive care unit [7,8]. A study showed the superiority of tPCO2 to end tidal CO2 and suggested that upper airway muscle weakness due to propofol is the reason that end tidal CO2 monitoring is not useful [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with this, although derived on a purely empirical basis. It might be of interest that there are multiple other uses of capnography beyond diagnostic applications, particularly in anesthesiology and bronchoscopic interventions [28], in which the end-tidal CO 2 concentration plays a major role. We did not evaluate this parameter, but it might well be related to AreaVol s3, which we used for diagnostic purposes.…”
Section: Ratio Area/volume Of Phasementioning
confidence: 99%